الإعداد المتكامل لمعلمي الرياضيات باستخدام التكنولوجيا في ظل ثورة المعلوماتية - عبدالله, نهى عمر; عثمان, عزالدين محمد; كرونيه, يوهانس (Journal of Faculty of Education, 2021)
This paper is about preparing Mathematics teachers in information era. TPACK framework which invites to integration between Technology, Pedagogical, and Content Knowledge to prepare teacher to integrate ICT in education was used. Data was collected using: questionnaires, and a workshop, interview, and observation. The study sample was composed of: teachers of Mathematics in faculties of Education and faculties of Science of Sudanese universities in Khartoum State, as well as teachers of Mathematics in secondary schools in the state, Educators in faculties of Education, and Computer teachers in Computer colleges, and graduates of colleges of Education )specializing in Mathematics(. In addition to: the deans of faculties of Education, and the heads of the departments of Mathematics, and the chairmen and members of committees to develop mathematics teacher preparation programs. A preliminary questionnaire was distributed to benefit from its results in dividing the respondents into three groups: those with limited experience in using technology in the teaching of Mathematics, those with intermediate experience, and the experts. A workshop on the use of technology for teaching Mathematics was carried out. After the workshop the questionnaire of the study was distributed. Interviews were also conducted with the makers and executors of the decision on mathematics teacher preparation. The collected data were analyzed by Excel and SPSS. Number of results were reached, it included: providing the student teacher with the knowledge and skills )in integration between the pedagogical knowledge, technological knowledge, and content knowledge _ specialization; according to TPACK framework( with the quality and depth which is appropriate in the minimum in making the student teacher able in the integrating technology in his\ her teaching according to the available tools and aids in order to achieve the educational goals and objectives of the subject, while providing in the maximum for the outstanding student teacher for innovating technological aids and new teaching methods. Also, the results pointed to the necessity of taking care of the appropriate environment of the preparation the things which will help in gaining that knowledge and skills; and the preparation policy should take into account the developments of the continuous preparation of the technological development. Therefore, we recommend considering these results when planning or developing teacher preparation program, specifically Mathematics teacher preparation program.